Evaluation of The Sustainability of The Green Open Space Program in Urban Development in DKI Jakarta - Gitami, Diyadzra Siti; Sunkar, M. Didan Abdillah; Sridevi, Raynita Monica (Proceedings of the International Conference on Green Technology; Vol 15 No 1 (2025): Proceeding of 15th International Conference on Green TechnologyDO - 10.18860/icgt.v15i1.3826, 2026)
The rise of development projects in the city of Jakarta has taken over green open space with the construction of tall buildings which has caused a decline in the quality of clean air for the community. The existence of green open space (RTH) will improve urban air quality. The research aims to evaluate the suitability of green open space (RTH) in Jakarta based on the Minister of ATR KBPN RI Regulation No. 14 of 2022 Chapter II Article 3. This research was carried out using quantitative methods and secondary data obtained from research journals and Jakarta government statistical data. The results of this research show that green open space in cities in Jakarta has increased in the last five years, from 1.20% in 2020 to 6.51% in 2024 of the DKI Jakarta area of 645.2 km² with a population of 10,684,900 people. It is necessary to increase green open space (RTH) by 23.49% in accordance with government regulations to meet community needs in improving air quality. The main strategy is mapping potential land such as government-owned assets as an alternative for providing green open space and conducting a comprehensive evaluation of program implementation involving various supportingparties.